Relationship between the neutrophil-to-lymphocyte ratio or platelet-to-lymphocyte ratio and deep venous thrombosis (DVT) following femoral neck fractures in the elderly - Shuai Niu; Yueying Pei; Xin Hu; Dianzhu Ding; Guangwei Jiang (Frontiers in Surgery, 2022)
PurposeThis study aimed to investigate whether the neutrophil-to-lymphocyte ratio (NLR) or platelet-to-lymphocyte ratio (PLR) was associated with deep venous thrombosis (DVT) following femoral neck fractures in the elderly.MethodThis was a retrospective cohort study and used data extracted from the hospitalization electronic medical record and the laboratory biomarker reports. Patients were included if they were aged above 60 years with a definite diagnosis of femoral neck fracture caused by low-energy trauma. Duplex ultrasound scanning was routinely performed to detect the potential DVT. Two independent multivariate logistic regression models were constructed to identify the association of NLR or PLR with the risk of DVT.ResultsA total of 708 patients with femoral neck fractures were included, and 112 were found to have DVT, indicating an incidence rate of 15.8%. There were significant differences across five subgroups for NLR or PLR, in terms of age (p = 0.020, 0.006), white blood cell (p < 0.001, =0.006), hemoglobin (p < 0.001, <0.001), and albumin (p < 0.001, <0.001). BMI was tested to be significantly different across subgroups for NLR (p = 0.030) and prevalence of cerebrovascular disease for PLR (p = 0.014). The multivariate analyses demonstrated that not NLR but PLR in Q3 (range, 179–238) was associated with an increased risk of DVT, and the risk for the latter was 1.86 (95%CI, 1.07–3.36).ConclusionWe concluded that a PLR value of 179–238 was associated with a 1.86-fold increased risk of DVT after femoral neck fracture. This study paves the way toward further exploration of inflammatory/immune biomarkers with the risk of DVT in the elderly with trauma.